Faith healing: the threat of "Surucucu" and the local cure of Amazon floodplain dwellers - Beatriz Nunes Cosendey; Juarez Carlos Brito Pezzuti (BMC, 2024)
Abstract Background Snakebites are considered a neglected tropical disease responsible for many accidents, some fatal, and are related to poverty. The Brazilian Amazon has the highest incidence of snakebites per inhabitant, with the state of Pará having the most reported cases. For those who have difficult access to hospitals and pharmacies, this issue is even more urgent. Methods In this research, we worked together with the population of five riverine communities in Aritapera (Santarém-PA), a fluvial island located in the Lower Amazon floodplain (várzeas), in order to identify the species of venomous snakes and create a record of snakebites in the region and treatments carried out. Results Dwellers reported a high frequency of encounters throughout the year and mentioned five venomous ethnospecies, although we identified only Bothrops atrox. Approximately 28.7% of the participants had already been bitten, and in 15.8% of the interviews, they mentioned deaths from snakebites. The treatments varied between hospitalization (42.8%), home treatments (23.8%), both together (25.4%) and healers (7.9%). There were cases where no treatment, or just religious treatment, was performed. In general, no serious sequelae were reported. Although home treatments were more common in the past, many people maintained the practice of using them before going to the hospital. Among the most used are Pau X and the fat of the Amazon River Dolphin. The latter appears to be a recent discovery by locals and is considered very efficient both for humans and animals. Conclusion Difficult access to health centers, a lack of energy to store antivenom and a high rate of encounters with snake place Aritapera dwellers in a vulnerable situation regarding snakebite accidents. In this context, they discovered treatments that improved their well-being until hospitalization. As the Amazon River dolphin is an endangered species, the use of its fat requires attention. In this sense, the dissemination of this knowledge is important to encourage studies that investigate which properties of this fat act as counterpoisons. By discovering substitutes that can be incorporated in other rural and remote communities, an economic and ecologically viable option for the health of residents can be promoted, in addition to valuing traditional knowledge.